PENGGUNAAN LABORATORIUM RIIL DAN VIRTUIL PADA PEMBELAJARAN FISIKA DENGAN MODEL INKUIRI TERBIMBING DITINJAU DARI KEMAMPUAN MATEMATIS DAN KETERAMPILAN BERPIKIR KRITIS - Matsun, Matsun; Sunarno, Widha; Masykuri, M (Jurnal Pendidikan Fisika, 2016)
This research aims at finding outÂ  the differences and interaction ofÂ  the implementation of teaching media, mathematical capability, and critical thinking towards the studentsâ learning achievement. The method used in this research is experimental method. The population was all IV semester students of Physics Education Department of IKIP PGRI Pontianak in the academic year of 2015/2016. The writer used cluster random sampling to get the sample. Data analysis was done by using three ways anava variansÂ  analysis. Based on the data analysis, it can be concluded that: 1) there are differences of cognitive and affective learning achievement to the students who are taught by using guided inquiry model with real and virtual laboratory; 2) there are differences of studentsÂ  cognitive learning achievementÂ  with high and low mathematical capability; 3) there are differences to psychometric learning achievement to the students who have high and low critical thinking; 4) There is no interaction between Guided Inquiry ModelÂ  using real and virual laboratory, high and low mathematical capability, andÂ  high and low critical thinking towards the studentsÂ  learning achievement.